MENINGKATKAN KEMAMPUAN SPATIAL SENSE DAN PEMECAHAN MASALAH MATEMATIK SISWA SMA MELALUI PENDEKATAN BERBASIS MASALAH - Nurkholis, Encep (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
This paper presents the findings from a pretest-posttest experimental control group design conducted by using problem based learning   assisted with  computer program to investigate students’ spatial sense  and problem solving  abilities.The study involved  72 grade-10 students in Karangununggal. The instrumens in this study are spatial sense and mathematical problem solving abilities tests, and opinion scale. The study found that: a) The problem based learning   assisted with  computer program was able to improve students’ spatial sense  and mathematical problem solving  abilities much better than the conventional approach. Spatial sense and mathematical  problem solving  abilities of students taught by using problem based learning   assisted with  computer program were classified as fairly good, whereas  those abilities of students taught by conventional teaching were classified as mediocore.  Nevertheless, there were no difference on the gain of those students’abilities of the both classes; b) There was high association between spatial sense and mathematical  communication abilities; c) Students performed positive opinion and enthusiastic toward  problem based learning   assisted with computer program